Synthesis and characterization of liquid crystalline unsymmetrically substituted phthalocyanines - Yüksel, Fatma; Atilla, Devrim; Ahsen, Vefa (Pergamon-Elsevier Science Ltd, 2007)
The synthesis of unsymmetrically substituted phthalocyanines bearing two p-tolyl-sulfonyl (tosyl)amido and six alkylthio moieties was achieved by cyclotetramerisation of two different phthalonitrile derivatives, namely 1,2-di(alkylthio)-4,5-dicyanobenzene and 4,5-dicyano-N,N'-ditosyl-o-phenylen(diamine in the presence of an anhydrous metal salt and strong base. The new compounds were characterized by elemental analyses, UV/Vis, IR, NMR and mass spectra. The mesogenic properties of these new materials were studied by differential scanning calorimetry (DSC) and polarizing optical microscopy. The mesogenic properties of these compounds were compared to that of their symmetric analogous, octaalkythia substituted plithalocyanine derivatives. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; asymmetric phthalocyanine; liquid crystal; metallomesogen